Measuring service quality using SERVQUAL model : a case study of e-retailing in Iran - Siadat, Seyed Hossein (2008)
Service quality is a concept that has aroused considerable interest and debate in the research literature because of the difficulties in both defining and measuring it with no overall consensus emerging on either. Customer satisfaction and service quality are often treated together as functions of customerâ€™s perceptions and expectations and research has shown that high service quality contribute significantly to profitability. Service quality is required to be first measured in order to improve the quality in a service organization. Practitioners and academics are eager on measuring service quality accurately in order to have better understanding of its indispensable antecedent and consequences, and eventually ascertain methods for improving and measuring service quality in search for competitive advantage. The aim of this study is to rank the dimensions of service quality that affect the customersâ€™ expectation in online purchasing in Iran from the customersâ€™ perspective. A questionnaire used in this study was published in Cloob.com which is an Iranian virtual society website. The measurements used were based on the widely accepted SERVQUAL model which is the most common method for measuring service quality. A descriptive statistics analysis was used to evaluate the level of service quality of Iranianâ€™s online shops from the customersâ€™ perspective. This study also examined the service quality gap by comparing customersâ€™ expectations and their actual perceptions. The results of the study indicated that all of the service quality factors are important. The â€œAccess is fastâ€? is the most important factor among the others and respondents are not satisfied with current connection speed although they are fine with extra services. Tangibility was rated as the most important dimension followed by assurance, reliability, responsiveness, and empathy.